Pengembangan Media Articulate Storyline dalam Pembelajaran Menulis Puisi pada Kelas X SMA Negeri 2 Sukabumi - Mardiyani, Ranny; Deden Ahmad Supendi; Fauziah Suparman (GERAM: Gerakan Aktif Menulis, 2021)
Learning media is one of the supporting facilities in teaching and learning activities. In this time of the COVID-19 pandemic, online-based learning media is very necessary. The lack of teacher ability in using interactive learning media makes online learning even more boring, especially in learning to write poetry. The articulate storyline is one software that can produce more interesting learning media. Using many features can produce learning media that are more varied, innovative, and easy to use. The research method used is RND, which has ten research steps that the researchers then simplified into four main steps, namely the research and data collection stage, the planning stage, the product development stage, and the validation and testing stage. Media development results are a product of a poem made by class X students at SMA Negeri 2 Sukabumi. The product was produced after learning poetry material using online interactive learning media. Three validators assessed the media feasibility level. The material validator is given a feasibility value of 82%, the medium validator is given a value of 80%, and the Indonesian language learning validator is given 84%. Meanwhile, 89% of students responded "Ya" in student responses, and 11% of students responded "Tidak". Based on the validator's assessment results, the media was considered very feasible to be used in schools and received a positive response from students.